Juan Pablo Ii in the Araucania. Catholic Church and Mapuche People in Chile (1961-1987) - Samaniego-Mesias, S (UNIV SIMON BOLIVAR, 2017)
We propose to think the national and international situation which took place when the Pope visited Chile under the dictatorship historically and, in particular, its mass meeting with members of the mapuche people. We explain why it was relevant for the transition to democracy and the vision of the Catholic Church concerning indigenous emergence in Latin America . The complex process of changes concerning the representations of the Church regarding the mapuche people from the Second Vatican Council and the Conference of Latin American Bishops in Medellin (1968) and Puebla (1979) is analyzed. We focus by means of historiography the speech H.H. John Paul II delivered to Chilean and Mapuche peasants during his visit to the country in Temuco, April 1987.